Power, greed, and hubris : judicial bribery in Mississippi - Crockett, James R. (Jackson : University Press of Mississippi, 2014)
"From 2003 to 2009 sensational judicial bribery scandals rocked Mississippi's legal system. Famed trial lawyers Paul Minor and Richard (Dickie) Scruggs and renowned judge and former prosecutor Bobby DeLaughter proved to be the nexus of these scandals. Seven attorneys and a former state auditor were alleged to have attempted to bribe or to have actually bribed five state judges to rule in favor of Minor and Scruggs in several lawsuits. This is the story of how federal authorities, following up on information provided by a bank examiner and a judge who could not be bribed, toppled Minor, Scruggs, and their enablers in what was exposed as the most significant legal scandal of twenty-first-century Mississippi. James R. Crockett details the convoluted schemes that eventually put three of the judges, six of the attorneys, and the former auditor in federal prison. All of the men involved were successful professionals and three of them, Minor, Scruggs, and fellow attorney Joey Langston, were exceptionally wealthy. The stories involve power, greed, but most of all hubris. The culprits rationalized abominable choices and illicit actions to influence judicial decisions. The crimes came to light in those six years, but some crimes were committed before that. These men put themselves above the law and produced the perfect storm of bribery that ended in disgrace. The tales Crockett relates about these scandals and the actions of Paul Minor and Dickie Scruggs are almost unbelievable. Individuals willingly became their minions in power plays designed to distort the very rule of law that most of them had sworn to uphold"--
Did Attorney Paul Minor Seek Unfair Advantages by Bribery? -- Paul Minor, Wes Teel, and John Whitfield : The Second Trial -- The Diazes' Income Tax Follies -- The Appeals of Minor, Teel, and Whitfield -- The Enigma That Is Richard F. "Dickie" Scruggs -- The Undoing of Dickie Scruggs -- Jones v. Scruggs and the Rise and Fall of the Scruggs Katrina Group -- The Odd Couple : Tim Balducci and Steve Patterson -- Who Is Judge Henry Lackey? -- Sentencing of the Scruggs I Defendants -- Joey Langston Violates His Own Rule -- The Bobby DeLaughter Tragedy -- Bobby DeLaughter Lied -- The Scruggs-Luckey-Wilson Legal Entanglement : Will This Thing Ever End? -- Presley L. "P. L." Blake and Edward J. Peters : The Teflon Men -- Zach and Dickie Scruggs's Appeals.
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Palo Alto, Calif. : ebrary, 2013. Available via World Wide Web. Access may be limited to ebrary affiliated libraries.
Keywords: Scruggs, Dickie -- Trials, litigation, etc; Trials (Bribery) -- Mississippi; Judicial corruption -- Mississippi; Practice of law -- Corrupt practices -- Mississippi; Electronic books